Antimalarial Effects of Iranian Flora Artemisia sieberi on Plasmodium berghei In Vivo in Mice and Phytochemistry Analysis of Its Herbal Extracts. (23rd January 2012) - Nahrevanian Nahrevanian, Hossein Hossein; Sheykhkanlooye Milan Sheykhkanlooye Milan, Bayram Bayram; Kazemi Kazemi, Masoud Masoud; Hajhosseini Hajhosseini, Reza Reza; Soleymani Mashhadi Soleymani Mashhadi, Soudeh Soudeh; Nahrevanian Nahrevanian, Shahab Shahab
Abstract : The aim of this study is pharmacochemistry of Iranian flora Artemisia sieberi and its antimalarial effects on Plasmodium berghei in vivo . This is the first application of A. sieberi for treatment of murine malaria. A. sieberi were collected at flowering stage from the Khorassan and Semnan provinces of Iran; the aerial parts were air-dried at room temperature and then powdered. The powder was macerated in methanol, filtered with Bokhner hopper and solvent was separated in rotary evaporator. Total herbal extract was subsequently processed for ether and chloroform extracts preparation. The toxicity of herbal extract was assessed on naive NMRI mice with high, average and low doses; then pathophysiological signs were assessed. Finally, the antimalarial efficacy was investigated on two groups of Plasmodium berghei infected mice. Percentage of parasitaemia and pathophysiology were also evaluated. The results of this assessment showed no toxicity even by high concentration of herbal extract. A significant reduction in percentage of parasitaemia was observed; no alterations of hepatosplenomegaly and body weight were indicated in study group. A. sieberi extracts showed antimalarial effects against murine malaria with some efficacies on reducing pathophysiology. However, there is requirement to find the major component of this herbal extract by further studies.